Radiation field size and dose determine oncologic outcome in esophageal cancer - BATIREL, HASAN FEVZİ (BIOMED CENTRAL LTD, 2016)
Background: Locoregional recurrence is a major problem in esophageal cancer patients treated with definitive concomitant chemoradiotherapy. Approximately half of the patients fail locoregionally. We analyzed the impact of enlarged radiation field size and higher radiation dose incorporated to chemoradiotherapy on oncologic outcome. Methods: Seventy-four consecutive patients with histologically proven nonmetastatic squamous or adenocarcinoma of the esophagus were included in this retrospective analysis. All patients were locally advanced cT3-T4 and/or cN0-1. Treatment consisted of either definitive concomitant chemoradiotherapy (Def-CRT) (n = 49, 66 %) or preoperative concomitant chemoradiotherapy (Pre-CRT) followed by surgical resection (n = 25, 34 %). Patients were treated with longer radiation fields. Clinical target volume (CTV) was obtained by giving 8-10 cm margins to the craniocaudal borders of gross tumor volume (GTV) instead of 4-5 cm globally accepted margins, and some patients in Def-CRT group received radiation doses higher than 50 Gy. Results: Isolated locoregional recurrences were observed in 9 out of 49 patients (18 %) in the Def-CRT group and in 1 out of 25 patients (3.8 %) in the Pre-CRT group (p = 0.15). The 5-year survival rate was 59 % in the Def-CRT group and 50 % in the Pre-CRT group (p = 0.72). Radiation dose was important in the Def-CRT group. Patients treated with > 50 Gy (11 out of 49 patients) had better survival with respect to patients treated with 50 Gy (38 out of 49 patients). Five-year survivals were 91 and 50 %, respectively (p = 0.013). Conclusions: Radiation treatment planning by enlarged radiation fields in esophageal cancer decreases locoregional recurrences considerably with respect to the results reported in the literature by standard radiation fields (18 vs > 50 %). Radiation dose is as important as radiation field size; patients in the Def-CRT group treated with = 50 Gy had better survival in comparison to patients treated with 50 Gy.
Keywords: Esophageal cancer; Concomitant chemoradiotherapy; Locoregional recurrence; Overall survival; SQUAMOUS-CELL CARCINOMA; POSITRON-EMISSION-TOMOGRAPHY; PHASE-II; PREOPERATIVE CHEMORADIOTHERAPY; NEOADJUVANT CHEMORADIOTHERAPY; CONCURRENT CHEMOTHERAPY; TRANSHIATAL RESECTION; CLINICAL-IMPLICATIONS; RECURRENCE PATTERN; RANDOMIZED-TRIAL